THE YELLOW WALLPAPER: A PSYCHOANALYTICAL PARALLELISM BETWEEN CHARACTER AND AUTHOR - M. Mohsin Manzoor; Razia Majeed; Safeer Haider; Muhammad Adnan Akbar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
A literary work always carries the impression of its author. Every piece of writing reveals something very essential about the person who creates it. However, some works of literature are considered to be autobiographical sketches of their authors. The Yellow Wallpaper was written by Charlotte Perkins Gilman, and this short story has a strong, resemblance with her life. Similarities between Charlotte's life and the protagonist of the story are very evident. The protagonist suffered from depression after giving birth to a child, and she was on the rest cure. Charlotte Perkin Gilman also suffered from the same kind of depression and she was advised a similar cure by the Doctor. So, it can be realized that every thought of the protagonist in the story is the thinking pattern of Charlotte. This story has been open to many interpretations but I want to interpret it through psychoanalysis. I intend to explore the similarities between Charlotte Perkins Gilman and the protagonist of this story based on psychoanalytic theory in general and defense mechanisms in particular.